Evaluation of the Factors Causing Cost and Time Overrun in the Namibian Construction Industry - Negussie, Menelik Gizaw (Department of Construction Economics and Management, 2023)
Cost and time are one of the two primary parameters that require due considerations throughout the project lifecycle and are the determining factors for project success. However, it is very common that many projects fail to achieve their goal of being completed within the planned budget and schedule. Several articles on cost and time overrun in the construction industry worldwide, holistically, and locally, were reviewed. However, limited studies were conducted in the Namibian construction industry. It is against this background that this study investigates the factors causing time and cost overrun in the Namibian construction industry and posits strategies to mitigate cost and time overrun on construction projects. The study adopted a quantitative research approach that employs a survey research design in data collection from a sample drawn from a population of professionals in the Namibian construction industry. The survey instrument — a questionnaire — was administered via email. The data collected was analysed using descriptive and inferential statistics comprising of means, percentages, Relative Importance Index (RII) and Spearman Correlation. The study found that five of the main factors contributing to cost overrun on the construction projects in Namibia from a ranking perspective are contractors' financial constraints, inadequate contractor experience, inefficient project planning and scheduling by the contractor, poor site management and delay in progress payment by the client. While the main causes of time overrun were found to consist of inadequate contractor experience, contractor's cashflow difficulty, poor site management and supervision, slow decision making by the client, and deficiency in project planning and scheduling by the contractor. Furthermore, this study revealed that four out of the five factors causing cost and time overrun are related to contractors, while one was client related. The study also found that key strategies proposed to mitigate cost overrun on projects from a ranking perspective include ensuring that consultants submit their drawings and documentations on time, frequent coordination between all the project parties and adequate project planning and scheduling. The key strategies proposed to mitigate time overrun, based on a ranking perspective, are proper planning of the work, adequate and close supervision of the project, and the consultant ensuring that drawings and documentations are submitted on time. Spearman correlation was carried out in order to measure the correlation between top ten rated cost and time overrun factors and construction performance. The result showed that there is positive correlation between cost and time overrun factors against construction performance however it was not statistically significant and this may be due to the small sample size . However, two of the top 10-time overrun factors — which include availability of finance of contractors, deficiency in project planning and scheduling, experience in project planning, late delivery of construction material and equipment, and extension of time claim cost overrun factors — showed a moderate and positive impact on construction performance. Further investigation of the hypothesis may be required. Based on these findings, the study concludes that projects on which an inexperienced contractor is engaged, and for which poor payment regimes exist, will experience time and cost overruns. The study recommends that activities undertaken at the execution stage should be properly monitored to prevent time and cost overruns on the project as a whole.